Integration of hedgehog and BMP signalling by the engrailed2a gene in the zebrafish myotome - Maurya, Ashish K.; Souren, Marcel; Wittbrodt, Joachim (Development, 2011)
Different levels and timing of Hedgehog (Hh) signalling activity have been proposed to specify three distinct cell types in the zebrafish myotome. Two of these, the medial fast-twitch fibres (MFFs) and the slow-twitch muscle pioneers (MPs) are characterised by expression of eng1a, -1b and -2a and require the highest levels of Hh for their specification. We have defined a minimal eng2a element sufficient to drive reporter expression specifically in MPs and MFFs. This element binds both Gli2a, a mediator of Hh signalling, and activated Smads (pSmads), mediators of bone morphogenic protein (BMP) signalling, in vivo. We found a strict negative correlation between nuclear accumulation of pSmad, and eng2a expression in myotomal cells and show that abrogation of pSmad accumulation results in activation of eng2a, even when Hh signalling is attenuated. Conversely, driving nuclear accumulation of pSmad suppresses the induction of eng expression even when Hh pathway activity is maximal. Nuclear accumulation of pSmads is depleted by maximal Hh pathway activation. We show that a synthetic form of the Gli2 repressor interacts with Smad1 specifically in the nuclei of myotomal cells in the developing embryo and that this interaction depends upon BMP signalling activity. Our results demonstrate that the eng2a promoter integrates repressive and activating signals from the BMP and Hh pathways, respectively, to limit its expression to MPs and MFFs. We suggest a novel basis for crosstalk between the Hh and BMP pathways, whereby BMP-mediated repression of Hh target genes is promoted by a direct interaction between Smads and truncated Glis, an interaction that is abrogated by Hh induced depletion of the latter.